2023
DOI: 10.1021/acs.macromol.2c02233
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis and PISA Behavior of Molecular Bottlebrush Block Copolymers via a Grafting-From Strategy through RAFT Dispersion Polymerization

Abstract: Precise synthesis of molecular bottlebrushes (MBBs) with high yield via the grafting-from strategy using a reversible deactivation radical polymerization (RDRP) technique has remained elusive. Herein, the molecular bottlebrush block copolymers (MBB BCPs) with high yield and varying chemical compositions were synthesized via a polymerization-induced self-assembly (PISA)-assisted grafting-from strategy by reversible addition–fragmentation chain transfer (RAFT) dispersion polymerization. First, the poly(norbornen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Up to now, a variety of approaches have been developed for the synthesis of MBBs, which can be summarized into three strategies, including grafting-from, grafting-onto, and grafting-through. Among these approaches, the grafting-through strategy combined with ring-opening metathesis polymerization (ROMP) of macromonomers (MMs) is promising, since precise MBBs with a perfectly accurate grafting density of 100% and block sequence can be easily synthesized. However, for preparing water-soluble MBBs with functional groups, such as tertiary amine and hydroxy groups, there are particularly clear challenges due to the inevitable catalyst decomposition induced by MMs with electron-donating groups as well as polar or protic solvents, leading to ROMP with low initiation efficiency and slow polymerization kinetics. Recently, O’Reilly , and Pokorski et al reported that the presence of chloride ions could significantly suppress the decomposition of the Grubbs catalyst and lead to better control of polymerization, which provides a great opportunity to synthesize water-soluble polynorbornenes (PNB) via aqueous ROMP. However, considering the above-mentioned challenges of synthesis of water-soluble MBBs, as far as we know, reports so far have been rarely reported to directly synthesize water-soluble MBBs by using aqueous ROMP via the grafting-through strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, a variety of approaches have been developed for the synthesis of MBBs, which can be summarized into three strategies, including grafting-from, grafting-onto, and grafting-through. Among these approaches, the grafting-through strategy combined with ring-opening metathesis polymerization (ROMP) of macromonomers (MMs) is promising, since precise MBBs with a perfectly accurate grafting density of 100% and block sequence can be easily synthesized. However, for preparing water-soluble MBBs with functional groups, such as tertiary amine and hydroxy groups, there are particularly clear challenges due to the inevitable catalyst decomposition induced by MMs with electron-donating groups as well as polar or protic solvents, leading to ROMP with low initiation efficiency and slow polymerization kinetics. Recently, O’Reilly , and Pokorski et al reported that the presence of chloride ions could significantly suppress the decomposition of the Grubbs catalyst and lead to better control of polymerization, which provides a great opportunity to synthesize water-soluble polynorbornenes (PNB) via aqueous ROMP. However, considering the above-mentioned challenges of synthesis of water-soluble MBBs, as far as we know, reports so far have been rarely reported to directly synthesize water-soluble MBBs by using aqueous ROMP via the grafting-through strategy.…”
Section: Introductionmentioning
confidence: 99%
“…133 Establishing protocols that make use of the advantages of heterophase systems, such as PISA, may hold promise in achieving complex architectures at high solid content. 73 Emulsion-confined self-assembly has demonstrated its potential to produce nanodiscs and toroids, but exhibits further untapped potential, especially in using discrete nanoparticles in conjunction with (co)polymers. 274 Similarly, the use This journal is © The Royal Society of Chemistry 2024 of pre-segmented polymer particles, like MPBs, adds another feature to this type of self-assembly as MPBs are both a nanoparticle as well as a giant copolymer-like macromolecule.…”
Section: Discussionmentioning
confidence: 99%
“…Starting with a sequential ROMP to design AB-type tad-pole bottlebrushes, with one block as a PEG bottlebrush and the other block as a poly-RAFT agent, they used this polymer as an amphiphile in the RAFT dispersion polymerisation of styrene. 73 During RAFT polymerisation, PS was grafted from the CTA-containing block in a PISA process to afford a series of MPBs with different hydrophobic/hydrophilic ratios by varying the length of the PS sidechains. At lower monomer conversion (shorter chain lengths), 35–59 nm spherical micelles formed, fusing to form 109 nm ellipsoids and then discs with a 46 nm thickness as monomer conversion and chain length increased.…”
Section: Polymer Nanoscale Discsmentioning
confidence: 99%
“…The NB-terminated poly(ethylene glycol)-monomethyl ether (NB-PEG, M n = 2.1 kDa) macromonomers (MMs) were synthesized by the esterification of PEG and NB carboxylic acid derivative, as reported in our previous work. 39 In the ME-ROMP, the water-soluble monomers could serve as surfactants to promote the formation of CH 2 Cl 2 /H 2 O emulsions (Figure S4a). Evidence of emulsion was further supplied by the optical micrographs of CH 2 Cl 2 /H 2 O emulsion (v/v = 1/10) with M1 as monomer, as shown in Figure S4b.…”
mentioning
confidence: 99%
“…The synthesis and characterizations are provided in the Supporting Information, as shown in Synthetic Procedures and Figures S1–S3. The NB-terminated poly­(ethylene glycol)-monomethyl ether (NB-PEG, M n = 2.1 kDa) macromonomers (MMs) were synthesized by the esterification of PEG and NB carboxylic acid derivative, as reported in our previous work …”
mentioning
confidence: 99%